Neuere Beiträge zur Kenntnis der Wirte der Braconiden (Hymenoptera: Braconidae). - Györfi, Ján (Contributions to Entomology = Beiträge zur Entomologie, 1959)
The author enumerates 22 species of Braconidae reared in Hungary within the last years from hitherto unknown hosts, including species of which a host species was unknown at all.